What Is Special in the Economics of Cybersecurity and Privacy? - Nicola Jentzsch (Waterford Institute of Technology (WIT), 2015)
One of the most popular questions in information security economics is whether there are any special features relating to privacy and cyber-security products and services that separate these from traditional goods, like apples or cars. This paper is a contribution to this discussion. First, different goods and services are compared to assess whether privacy and cyber-security are in fact different. Although basic, it is enlightening. We then discuss how economics treats key features and whether the observed differences justify any `special' terminology.
info:eu-repo/grantAgreement/EC/FP7/609892
Keywords: 330; Datensicherheit